2017
DOI: 10.1177/0022034517709005
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of Gap Progress during and after Composite Polymerization

Abstract: The aims of this study were to observe the behavior of composite and formation of gaps during and immediately after light polymerization using swept source optical coherence tomography (OCT) and to compare the interfacial integrity of adhesives in cavities through 3-dimensional (3D) image analysis. Forty tapered cylindrical cavities (4-mm diameter, 2-mm depth) were prepared in bovine incisors and restored using Bond Force (BF), Scotchbond Universal Adhesive (SBU), OptiBond XTR (XTR), or Clearfil SE Bond 2 (SE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…Recently, SS-OCT has been used for the detection of caries, tooth fractures, and secondary caries at the restoration-tooth interface in vivo and in vitro 6,28) . Additionally, some studies have demonstrated that SS-OCT can be used for the quantitative measurement of gaps between resin composite and cavity walls 32) and observation of real-time gap progression 26) . A recent study using SS-OCT observation, reported that internal gap formations in resin composite restorations were correlated with the shrinkage parameters of resin composites 3) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, SS-OCT has been used for the detection of caries, tooth fractures, and secondary caries at the restoration-tooth interface in vivo and in vitro 6,28) . Additionally, some studies have demonstrated that SS-OCT can be used for the quantitative measurement of gaps between resin composite and cavity walls 32) and observation of real-time gap progression 26) . A recent study using SS-OCT observation, reported that internal gap formations in resin composite restorations were correlated with the shrinkage parameters of resin composites 3) .…”
Section: Discussionmentioning
confidence: 99%
“…Collected backscattered light from the sample is returned to the system, digitized in time scale, and analyzed in the Fourier domain to form a depth-resolving scan (A-scan) at each point. A serial set of A-scans along a certain section creates a row data file of back-scattered signal intensity (B-scan) and a 2-dimensional cross-sectional (2D) image 26) .…”
Section: ) Ss-oct Optical Observation Of Surface Displacementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current treatment protocols advocate bonded sealing for a variety of reasons. These include increased mechanical stability of the restoration due to an improved distribution and resistance to stresses, as well as prevention of bacterial percolation at the interface (Hayashi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%